2018
DOI: 10.2987/17-6707.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Distribution, Blood-Feeding Habits, and Viruses of Mosquitoes in an Open-Faced Quarry in Connecticut, 2010 and 2011

Abstract: Seasonal abundance of mosquitoes, their viruses, and blood-feeding habits were determined at an open-faced quarry in North Branford, CT, in 2010 and 2011. This unique habitat had not previously been sampled for mosquitoes and mosquito-borne viruses. Thirty species of mosquitoes were identified from 41,719 specimens collected. Coquillettidia perturbans, Aedes trivittatus, and Ae. vexans were the most abundant species and represented 34.5%, 17.7%, and 14.8% of the totals, respectively. Jamestown Canyon virus was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…However, other studies have shown mammals other than humans to be the primary source of blood meal. In Maryland, 50% of blood meals originated from rats [ 29 ], and multiple studies have shown that most blood meals (53–100%) were derived from white-tailed deer [ 36 39 ]. The frequency of white-tailed deer as hosts for Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies have shown mammals other than humans to be the primary source of blood meal. In Maryland, 50% of blood meals originated from rats [ 29 ], and multiple studies have shown that most blood meals (53–100%) were derived from white-tailed deer [ 36 39 ]. The frequency of white-tailed deer as hosts for Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in the northeastern United States have found that white-tailed deer, the most abundant large mammal in the region, represent the majority of blood meals identified from Ae. japonicus [ 36 39 ]. But other mammalian hosts have also been identified including the domestic cat [ 29 , 40 ], brown rat [ 29 ], opossum [ 38 ], cow [ 41 ], chipmunk [ 37 ], and horse [ 36 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aedes canadensis is distributed throughout Canada as well as the Northern, Eastern, and Midwestern states in the U.S.A ( 29 ). This species does take blood meals from deer ( 28 , 30 33 ). Jamestown Canyon virus was detected in 2 studies from field-collected adult female Ae .…”
Section: Discussionmentioning
confidence: 99%
“…The ability of An. punctipennis to transmit arboviruses such as Cache Valley [12] and eastern equine encephalomyelitis [13] viruses, as well as a nematode Diro llaria immitis [14] has also been reported.…”
Section: Introductionmentioning
confidence: 99%